2006
DOI: 10.1016/j.jvs.2005.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Simulator assessment of innate endovascular aptitude versus empirically correct performance

Abstract: Although inherently subjective, the MRS yields reproducible scores that correlate with endovascular experience and formal training. Experts and novices with extensive video game experience achieve short completion times, whereas high MRS scores are achieved only by formally trained subjects. Innate endovascular aptitude and empirically correct performance may be two separate things, and aptitude may be acquirable through (or identified by) extensive nonmedical video game experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 11 publications
(8 reference statements)
2
50
0
Order By: Relevance
“…These studies have demonstrated that the global rating scales tend to be more sensitive to levels of expertise (Regehr et al 1998;Goff et al 2002Goff et al , 2005Broe et al 2006), which is consistent with evidence in the OSCE literature regarding checklists and global ratings (Hodges et al 1999;Hodges and McIlroy 2003). Based on this evidence (in addition to the higher inter-rater reliabilities and inter-station correlations for the global rating scales), some investigators have opted to rely solely on the global rating when implementing an OSATS examination (Bann et al 2003;Datta et al 2004;Hance et al 2005;Hislop et al 2006;Leong et al 2008;Kassab et al 2011). This approach seems reasonable based on the limited data that are available, but we also point out that the inter-rater reliabilities for the checklists are generally substantial (and higher than those described for OSCEs).…”
Section: Relationships With Training Levelssupporting
confidence: 69%
See 3 more Smart Citations
“…These studies have demonstrated that the global rating scales tend to be more sensitive to levels of expertise (Regehr et al 1998;Goff et al 2002Goff et al , 2005Broe et al 2006), which is consistent with evidence in the OSCE literature regarding checklists and global ratings (Hodges et al 1999;Hodges and McIlroy 2003). Based on this evidence (in addition to the higher inter-rater reliabilities and inter-station correlations for the global rating scales), some investigators have opted to rely solely on the global rating when implementing an OSATS examination (Bann et al 2003;Datta et al 2004;Hance et al 2005;Hislop et al 2006;Leong et al 2008;Kassab et al 2011). This approach seems reasonable based on the limited data that are available, but we also point out that the inter-rater reliabilities for the checklists are generally substantial (and higher than those described for OSCEs).…”
Section: Relationships With Training Levelssupporting
confidence: 69%
“…Of the included studies, an OSATS for obstetrics and gynecology training has shown increasing scores after additional laboratory skills training VanBlaricom et al 2005) and prior training on an endovascular simulator is associated with subsequent higher OSATS ratings (Hislop et al 2006). While these studies demonstrate training improves performance in the simulation setting, support of the extrapolation argument would be stronger if the link between simulation-based performance and realworld proficiency had also been established.…”
Section: Relationships With Training Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper provides guidance on training medical students and vascular trainees as members of a simulated interventionalist team. different scenarios including those beyond their level of experience, prior to interventions performed on real patients (Dayal et al 2004;Aggarwal et al 2006;Hsu et al 2004;Van Herzeele et al 2007;Reznick & MacRae 2006;Patel et al 2006;Hislop et al 2006;Neequaye et al 2007a). There are several reasons for working with simulated teams.…”
Section: Practice Pointsmentioning
confidence: 99%